Strengthening Brazil's innovation policy through public procurement - Andre Tortato Rauen (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
Since the enactment of the Brazilian Innovation Law, the country has acquired valuable insights into the intricacies of the innovation process. This acquired knowledge is manifested in the updated New Law of Bidding and Contracts (NLBC), the revised Legal Framework for Startups, and the amended text of the original innovation law itself. These pioneering legislations have introduced a unique set of tools that foster innovation by leveraging the State's procurement power to stimulate private demand. This article aims to present the rationale behind these novel instruments from a neo-Schumpeterian perspective and the Technological Readiness Level methodology. By conducting an in-depth analysis of the legislation and incorporating recent theoretical contributions, we demonstrate for the first time that all stages of the innovative process are covered, including the "Death Valley" and the ambiguous transition between research and development (R&D) and innovation. As a result, ten public procurement instruments can be employed to promote private innovation. Among these, three are not innovation-specific, while one is entirely new. The remaining seven are specific to innovation, with four being completely original. Considering other traditional instruments that act on the supply side, we conclude that Brazil now possesses a powerful combination of innovative policy instruments, which necessitates advanced training for public employees.
Keywords: O38; O31; O32; 330; Public Procurement for Innovation - PPI; demand side innovation policies; Brazil